Displacement Limiters as Instigators of Large Amplitude Vibrations in Lightly Damped Systems - Feng, Z.C.; Lin, Yuyi (Journal of Vibration Testing and System Dynamics, 2026)
Displacement limiters also known as stoppers are rigid barriers used to limit the motion or to alleviate the load in mechanical design. This paper identifies conditions under which the stopper causes the motion to be trapped in large amplitude oscillations accompanied by violent impact with the stopper. Special focus is on those parameters for which the stopper was not expected to play any role based on the predicted linear steady-state responses.